Developing a research agenda for digital accessibility in multinational enterprises - Deitmer, A.; Silva, J. M. V.-B. da; Möhring, M. (Proccedings of the 29th International Annual EurOMA Conference, 2022)
Digital accessibility for disabled people is a hot topic of Corporate Social Responsibility, mandatory under current UN and UE dispositions. This research aims at investigating its company-wide administrative integration by developing a systematic process of enquiry producing a diagnosis tool under the guidance of the Soft Systems Methodology (RQ3). Absorptive capacity provided the theoretical umbrella for structuring the problem-situation (RQ1) by setting its Root Definitions. Thus, the expected scientifically supported diagnosing tool should generate feasible and desirable changes to the problem-situation perceptions (RQ2). Digital Accessibility by Design in Service was coined to define this innovative and relevant approach.